Financial performance appraisal of Atwima Kwanwoma Rural Bank - Benteh, Francis Afful (2011)
A Dissertation submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the Degree of Master of Business Administration.